2011
DOI: 10.1787/5kg0ps7zg6r8-en
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Asian Economic Integration

Abstract: Document complet disponible sur OLIS dans son format d'origine Complete document available on OLIS in its original format DSTI/DOC(2011)3 Unclassified English -Or. English Cancels & replaces the same document of 12 December 2011 DSTI/DOC(2011)3 2 STI Working Paper SeriesThe Working Paper series of the OECD Directorate for Science, Technology and Industry is designed to make available to a wider readership selected studies prepared by staff in the Directorate or by outside consultants working on OECD projects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Work at the country level (e.g. Fukasaku et al, 2011) has revealed greater country integration in Asia as a result of the fragmentation of production. Further, outcomes of an interregional input-output (IRIO) model for China (see Pei et al, 2011) have shown that the position of regions in the interregional and international supply chain is 18.10 Total interzonal Type II multipliers, Chicago, 2000 strongly related to the level of their income per capita.…”
Section: Interregional Models and Supply Chainsmentioning
confidence: 99%
“…Work at the country level (e.g. Fukasaku et al, 2011) has revealed greater country integration in Asia as a result of the fragmentation of production. Further, outcomes of an interregional input-output (IRIO) model for China (see Pei et al, 2011) have shown that the position of regions in the interregional and international supply chain is 18.10 Total interzonal Type II multipliers, Chicago, 2000 strongly related to the level of their income per capita.…”
Section: Interregional Models and Supply Chainsmentioning
confidence: 99%